Are Content-Specific Curricula Differentially Effective in Head Start or State Prekindergarten Classrooms? - Nguyen, Tutrang (AERA Open, 2018)
Head Start and state prekindergarten (pre-K) programs can boost the school readiness of low-income children through the use of effective preschool curricula. Encouraging results from some studies suggest that children who receive targeted or content-specific curricular supplements (e.g., literacy or math) during preschool show moderate to large improvements in that targeted content domain, but recent research also suggests differences in children’s school readiness among different preschool program settings. We examine whether children in Head Start or public pre-K classrooms differentially benefit from the use of randomly assigned classroom curricula targeting specific academic domains. Our results indicate that children in both Head Start and public pre-K classrooms benefit from targeted, content-specific curricula. Future research is needed to examine the specific mechanisms and classroom processes through which curricula help improve children’s outcomes.